Snow thickness measurements at ice station PS118_20190226_4 during POLARSTERN cruise PS118 - Arndt, Stefanie; Haas, Christian (In: Arndt, S; Haas, C (2021): Snow thickness measurements at ice stations during POLARSTERN cruise PS118 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.928966, 2021)
Snow depth measurements were obtained using a MagnaProbe (Snow-Hydro, Fairbanks, Alaska, USA) during walking surveys on most ice stations during PS118. The walks were randomly done on the entire floe. The MagnaProbe measurements were accompanied by measurements of the total sea-ice thickness with a ground-based multifrequency electromagnetic induction instrument (GEM-2) along the same transect.